PENGEMBANGAN KREATIVITAS MAHASISWA, WAKAKA™: WAHANA KARYA KEBIJAKSANAAN - Jodi Jodi; Shenniwaty Vesakha Putri; Imelda Selvia Lestari Sibarani; Sulaiman Sulaiman (Yayasan Education and Social Center, 2023)
Two students of the Buddhist Business and Management Study Program and a student of the Buddhist Counseling Psychology and Education Study Program, along with a lecturer at the Sriwijaya Buddhist College (STABN), the only group representing the Sriwijaya STABN won a competitive grant for the Student Creativity Program (PKM) in Entrepreneurship, 2022. Plastic waste is a life problem in many developing countries, including Indonesia. Various sophisticated tools have been invented through science and technology to recycle plastic waste into economically valuable recycled materials. Together with producer partners, the PKM-K group obtains finished products from t-shirts and hoodies. Inspired by the simplicity and wisdom of zen manifested in the artwork and calligraphy of Catera Zebuart™ design, which has intellectual property rights, the PKM-K group uses it as a screen-printed design on t-shirts and hoodies. Thus, the resulting product is named with the WAKAKA™ trademark: Wahana Karya Wisdom. PKM-K WAKAKA aims to (1) proclaim saving the earth by reducing plastic waste (reduce) reusing items that have been used (reuse), and using items from recycled materials (recycle); (2) inspiring the community through zen wisdom; (3) and for students themselves to practice Buddhist entrepreneurship that has been studied theoretically. Using Buddhist economic principles, 8% of the income from the sale of these WAKAKA products is funded by the Indonesian Buddhist Religious Paramitha Fund Program by the Directorate General of Buddhist Community Guidance, Ministry of Religion, Republic of Indonesia. During the four months the program has been running, from September to December 2022, up to 80 pieces have been sold, with a net profit of IDR 940.80, - (Nine hundred forty thousand eight hundred rupiahs). Based on its objectives, this program has been successfully implemented properly